Construção discursiva da liderança escolar dos professores: da praxis revolucionária ao tempo de normalização - Maria de Fátima Sanches Chorão (Universidade do Minho, 2004)
While approaching the teachers narrative discourse on the school governance during the revolution of 1974, this article gives emphasis to the following questions: (1) What features differenciate the teachers revolutionary discourse? (2) What ideas and motivations gave foundation and direction to the teachers school governance leadership? (3) What types of professionalism emerged in articulation with the teachers school governance praxis? The discourse analysis revealed concerns with social justice that radicates in a strong social conscience, and generated forms of social and political activism which found in school the center for a critical pedagogy, for a personal and societal transformation as well. In addition, the utopic and revolutionary style of leadership varied in correspondance to differential positions concerning school autonomy, logics of interaction between school and the Ministry of Education, and the possibility of constructing school based educational policies.